Structural, optical, and luminescence properties of ZnO:Ga optical scintillation ceramic - Gorokhova, Elena I.; Eronko, Sergey B.; Oreshchenko, E. A.; Sandulenko, Alexander V.; Rodnyǐ, Piotr A.; Chernenko, Kirill A.; Venevtsev, Ivan D.; Kulkov, Alexander M.; Muktepavela, Faina O.; Boutachkov, Plamen (OSA - The Optical Society, 2018)
This paper discusses the characteristics of ZnO and ZnO:Ga ceramics fabricated by uniaxial hot pressing. The short-wavelength transmission limit of zinc oxide ceramics is in the 370-nm region; the long-wavelength limit is determined by the free-charge-carrier concentration and lies in the interval from 5 to 9 μm. The total transmittance of such ceramics in the visible and near-IR regions is about 70% when the sample is 0.5 mm thick. The luminescence spectrum is represented by a broad emission band with maximum at 580 nm, having a defect nature. The introduction of 0.03–0.1 mass % gallium into the zinc oxide structure inhibits grain growth and increases the free-charge-carrier concentration to 3.44 × 1019 cm−3. As the gallium concentration increases in the range 0.05–0.1 mass % in a ceramic of composition ZnO:Ga, the defect luminescence band is suppressed and a characteristic exciton luminescence is formed with a maximum corresponding to 389 nm and a damping time constant of 1.1 ns.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics